Visual Recognition to Identify Helmet on Motorcycle Rider Using Convolutional Neural Network - Kevin Alexander; Rayhan Ardiya Dwantara; Raihan Muhammad Naufal; Derwin Suhartono (CommIT (Communication and Information Technology) Journal, 2020)
The amount of motorcycle accidents is increasing each year. The main reason is that the riders do not wear a helmet. The research aims to minimize the accident by training the machine learning using the IBM Watson Studio. It trains the data about “wearing helmet” and “not wearing helmet”. The used method is Convolutional Neural Network (CNN). About 170 image datasets are used. CNN is conducted on the input image using a kernel or filter. The filter will multiply its values with the overlapping values of the image while also sliding and adding them all to produce a single value for each of them until the entire images have passed and finished. After CNN method is done, the researchers can classify the images by using supervised learning. It can identify whether the rider is wearing a helmet or not simply by scanning a picture on the street. The result shows high accuracy of 92.87%. The method can be used to minimize the percentage of motorcycle accidents caused by not wearing a helmet.